Анализ зависимости виброускорений рабочих органов от последовательности разнонаправленных механических импульсов - Надутый, В. П.; Ягнюков, В. Ф.; Ягнюкова, И. В. (НТУ "ХПИ", 2014)
Цель данной работы состоит в описании и анализе траектории перемещения центра масс нелинейного маятника с параметрическим возбуждением для реализации разнонаправленных виброударных импульсов. Исследованы нормальное, радиальное и трансверсальное ускорения для центра масс нелинейного маятника. Определены зависимости ускорений от входной частоты колебаний вибровозбудителя, амплитуды исходных круговых колебаний, количества граней применяемых многоугольников и зазора между ними.

The research on the application of vibroimpact pulses have been widely studied in recent years be-cause of the fact the fact that such pulses are able to improve the screening performance. There is a new mechanical model of the nonlinear pendulum with parametric excitation is proposed in this paper for the implementation of directed vibroimpact pulses in the plane or space on the screening surface of the screen. The main objective of the study is to describe and analyze the trajectory of the center of mass of the pendulum. Normal, radial and transversal accelerations of the mass center of the nonlinear pendulum are studied; in particular the parameters often used in practice are applied in calculations. The dependen-cies of the acceleration on the input frequency oscillation exciter, the initial amplitude of circular oscilla-tions, number of polygons’ faces used in and the gap between them are defined.
The analysis of dependence of executive tools’ vibroaccelerations from multidirectional mechanical pulse sequence
Keywords: виброударные импульсы; нелинейный маятник; вибропривод грохота; ускорения импульсов; vibro-impact pulses; normal acceleration; radial acceleration; transversal acceleration; full acceleration; nonlinear pendulum